Addressing the Digital Divide in Contemporary Biology: Lessons from Teaching UNIX. Issue 10 (October 2017) - Mangul, Serghei; Martin, Lana S.; Hoffmann, Alexander; Pellegrini, Matteo; Eskin, Eleazar
Abstract : Life and medical science researchers increasingly rely on applications that lack a graphical interface. Scientists who are not trained in computer science face an enormous challenge analyzing high-throughput data. We present a training model for use of command-line tools when the learner has little to no prior knowledge of UNIX.